Rigorous Process for Isolation of Gut-Derived Extracellular Vesicles (EVs) and the Effect on Latent HIV - Nneoma C. J. Anyanwu; Lakmini S. Premadasa; Wasifa Naushad; Bryson C. Okeoma; Mahesh Mohan; Chioma M. Okeoma (Cells, 2025)
The human gastrointestinal (GI) track host trillions of microorganisms that secrete molecules, including extracellular vesicles (EVs) and extracellular condensates (ECs) that may affect physiological and patho-physiological activities in the host. However, efficient protocols for the isolation of pure and functional GI-derived EVs|ECs is lacking. Here, we describe the use of high-resolution particle purification liquid chromatography (PPLC) gradient-bead-column integrated with polyvinylpolypyrrolidone (PVPP)-mediated extraction of impurities to isolate EVs from colonic content (ColEVs). PVPP facilitates the isolation of pure, non-toxic, and functionally active ColEVs that were internalized by cells and functionally activate HIV LTR promoter. ColEVs isolated without PVPP have a reductive effect on MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) without living cells, suggesting that ColEVs contain reductases capable of catalyzing the reduction of MTT to formazan. The assessment of the origin of ColEVs reveals that they are composed of both bacteria and host particles. This protocol requires ~12 h (5 h preprocessing, 7 h isolation) to complete and should be used to purify EVs from sources contaminated with microbial agents to improve rigor. This protocol provides a robust tool for researchers and clinicians investigating GI-derived EVs and the translational use of GI-derived EVs for diagnostic and therapeutic use. Additionally, GI-derived EVs may serve as a window into the pathogenesis of diseases.